Analisis Inflasi di Indonesia: Penerapan Model Vitaliano - Rika Swastika; Taufiq Chaidir; Ida Ayu Putri Suprapti (Syntax Literate, 2023)
This study aims to analyze the case of inflation in Indonesia, which is based on the problem of raising the price level (inflation) which is a classic economic problem of various countries, especially developing countries such as Indonesia. In this study using the Vitaliano model to analyze inflation, the variables included in this model are the money supply (M2), economic growth as measured by gross domestic product and government spending. The analytical tool used in this study is the Error Correction Model, with the test results concluding that the variables of money supply, economic growth and government spending have no effect on inflation in either the short or long run.